EFFORTS TO IMPROVE THE WRITING ABILITY OF TEXT REPORTS OF OBSERVATION RESULTS OF STUDENTS CLASS VII MTS NURUL FALAH KOTA CIMAHI - Iis Islamiah; Ade Tina; Ika Mustika (IKIP Siliwangi, 2019)
This research is motivated by the students 'ability to write is still low, it is due to a lack of students' understanding of the material taught so that they are still confused to write and integrate words into full text. The purpose of this study is to determine the implementation of theprogram, lesson study especially in terms of improving the ability to write student observation report text. This type of research is Classroom Action Research (CAR) based on lesson study. The subject of this study was VII-F class students of MTs Nurul Falah, Cimahi City. The instruments used were observation sheets, RPPs, Student Worksheets (LKS), and test sheets of students' ability to write observational report text. The finding of this analysis is that implementing theprogram lesson study showed an increase in students' writing ability in the observation report text. This is known by the increasing number of students who show independence in the learning process, students are able to analyze the structure and rules of language contained in the text of the observation report. In addition, students are also able to compile the text of the observation report.